Facts-Signs and Cultural Sociology: How Meaning-Making Liberates the Social Imagination - Alexander, Jeffrey C. (Sociologija. Mintis ir veiksmas, 2010)
Translation: Editorial board is thankful to Jeffrey C. Alexander (Lillian Chavenson Saden Professor of Sociology, Yale University) for the publishing permission and hopes for a more intensive scientific cooperation between the sociologists of the United States of America and Lithuania.